Dual-channel near-field holographic MIMO communications based on programmable digital coding metasurface and electromagnetic theory - Rui Wen Shao; Jun Wei Wu; Jiachen Li; Shengguo Meng; Yifan Xu; Zheng Xing Wang; Wankai Tang; Qiang Cheng; Shi Jin; Tie Jun Cui (Nature Communications)
Abstract Holographic multiple-input multiple-output (MIMO) method leverages spatial diversity to enhance the performance of wireless communications and is expected to be a key technology enabling for high-speed data services in the forthcoming sixth generation (6G) networks. However, the antenna array commonly used in the traditional massive MIMO cannot meet the requirements of low cost, low complexity and high spatial resolution simultaneously, especially in higher frequency bands. Hence it is important to achieve a feasible hardware platform to support theoretical study of the holographic MIMO communications. Here, we propose a near-field holographic MIMO communication architecture based on programmable digital coding metasurface (PDCM) and electromagnetic theory. The orthogonal holographic patterns on the transmitting and receiving apertures are firstly obtained using the Hilbert-Schmidt decomposition of the radiation operator. Then the information to be transmitted is pre-encoded on PDCM following the principle of direct digital modulations. A PDCM-based holographic MIMO prototype is designed and experimentally verified in microwave frequencies. The measured results of constellations show that the prototype can realize dual-channel signal transmissions under quadrature-phase shift keying scheme. The proposed paradigm features low complexity, low cost and low power consumption, and may become a valuable technique in beyond fifth generation and 6G wireless communications.